"At Your Service": Sexual Harassment of Female Bartenders and Its Acceptance As "Norm" in Lagos Metropolis, Nigeria. Issue 9 (May 2022) - Aborisade, Richard A.
Notwithstanding the pervasiveness of sexual harassment in the bar and restaurant industry, limited attention has been paid to empirically examining the dynamics of sexual crimes committed in the industry. To address this, a qualitative study was conducted with female bartenders in drinking bars within Lagos metropolis to explore the nature and patterns of sexual harassments they experienced, as well as their response, coping measures and bar management's positions. Forty-seven interviews were conducted, and a thematic analysis of the narratives was carried out. Findings indicated that participants experienced a variety of unwanted sexual behavior from customers, coworkers and managers, including verbal expressions, signs, gestures and physical harassment that are sexual in nature. Although sexual harassment is ubiquitous, there was appreciable recognition of it as being undesirable and problematic with feelings of anger, fear, humiliation, shame, guilt, violation, powerlessness and loss of control. Participants hinged their vulnerability to being harassed on gender inequality, discrimination, feminization of poverty and sexual objectification of women in Nigerian society. These findings have important practical and policy implications if the sexual maltreatments of working women in Nigeria, especially in the low-income earning occupations, are to be acknowledged and addressed.